Morphology and isozyme variation among madeira vine (Anredera cordifolia) accessions from southeastern part of Central Java, Indonesia - RESTYKANIA; suratman; ARI PITOYO; SURANTO (Society for Indonesian Biodiversity, 2019)
Abstract. Restykania, Suratman, Pitoyo A, Suranto. 2019. Morphology and isozyme variation among madeira vine (Anredera cordifolia) accessions from southeastern part of Central Java, Indonesia. Biodiversitas 20: 3024-3032. The genetic diversity among madeira vine accessions from southeastern part of Central Java has not been investigated in detail. Information on genetic diversity and relationship among accessions of this plant will provide important input into determining resourceful management strategies and guiding the improvement of plants through plant breeding programs. The objective of this study was to evaluate variation of morphology and isozyme among madeira vine (Anredera cordifolia (Ten.) Steenis) accessions from southeastern part of Central Java. A total of 13 madeira vine accessions were used for morphological observations and isozyme analysis. Morphological diversity was characterized based on measurements and observations of vegetative structures such as stems, leaves, and aerial tubers. Identification of biochemical markers was done using peroxidase and esterase isozyme systems. A relationship dendrogram among accessions was constructed based on the genetic similarity matrix by applying a cluster analysis. The analysis of quantitative and qualitative morphological characters revealed that the majority of the tested traits showed variation, indicating that there was variability among the tested madeira vine accessions. Polymorphism was observed using isozyme of peroxidase (i.e. two banding patterns) and esterase (i.e. five banding patterns). Based on the dendrogram at a level of 63 % similarity, it showed distinct separation of 13 madeira vine accessions into two major clusters. Cluster I consisted of nine accessions and the closest relationship was shown between KLT 3 and KLT 1 accessions that had 94 % of similarity coefficient. The remaining four accessions were clustered separately as Cluster II with similarity coefficient of 73 %. Therefore, genetic characterization based on morphological and isozyme markers obtained in this study is valuable to understand genetic variability and relationship among madeira vine accessions in southeastern part of Central Java.